Australian private midwives with hospital visiting rights in Queensland: Structures and processes impacting clinical outcomes. Issue 6 (December 2017) - Fenwick, J.; Brittain, H.; Gamble, J.
Abstract: Background: Reporting the outcomes for women and newborns accessing private midwives with visiting rights in Australia is important, especially since this data cannot currently be disaggregated from routinely collected perinatal data. Aim: 1) Evaluate the outcomes of women and newborns cared for by midwives with visiting access at one Queensland facility and 2) explore private midwives views about the structures and processes contributing to clinical outcomes. Methods: Mixed methods. An audit of the 'all risk' 529 women receiving private midwifery care. Data were compared with national core maternity variables using Chi square statistics. Telephone interviews were conducted with six private midwives and data analysed using thematic analysis. Findings: Compared to national data, women with a private midwife were significantly more likely to be having a first baby (49.5% vs 43.6% p = 0.007), to commence labour spontaneously (84.7% vs 52.7%, p < 0.001), experience a spontaneous vaginal birth (79% vs 54%, p < 0.001) and not require pharmacological pain relief (52.9% vs 23.1%, p < 0.001). The caesarean section rate was significantly lower than the national rate (13% vs 32.8%, p < 0.001). In addition fewer babies required admission to the Newborn Care Unit (5.1% vs 16%, p < 0.001). Midwives were proud of their achievements. Continuity of care was considered fundamental to achieving quality outcomes. Midwives valued the governance processes embedded around the model. Conclusions: Private midwives with access to the public system is safe. Ensuring national data collection accurately captures outcomes relative to model of care in both the public and private sector should be prioritised.